Investigation of anterior scleral thickness in patients with corneal stromal dystrophies using swept-source anterior segment optic coherence tomography (Annals of Medical Research, 2024)
Aim: The distinctive feature of corneal dystrophies is the existence of abnormal deposits that are insoluble and found in different layers of the cornea. While corneal thickness has been investigated in corneal stromal dystrophies, anterior scleral thickness has not yet been evaluated. We aimed to investigate anterior scleral thickness and corneal and anterior segment parameters in corneal stromal dystrophies in this study.Materials and Methods: The study was conducted with 35 eyes with corneal stromal dystrophies from 19 patients and 35 healthy controls.  We calculated the anterior scleral thickness 4 mm posterior to the scleral spur in the nasal and temporal quadrants,  by anterior segment optic coherence tomography (Triton, Topcon, Japan). Scheimflug corneal tomography (Sirius, CSO, Italy) was performed to assess corneal and anterior segment parameters.Results: The mean age was 36.5±12.1 years in the dystrophy group. The mean temporal scleral thickness was 556.67±15.11 µm, and the mean nasal scleral thickness was 565.83±15.18 µm, statistically similar to those of the control group (p=0.81, p=0.51, respectively). However, the difference between temporal and nasal scleral thickness values was not statistically significant in the dystrophy group (p=0.53, p=0.57). Intraocular pressure was higher in lattice stromal dystrophy than in other dystrophies (p=0.005). There was found to be a moderate, positive correlation between age and nasal scleral thickness in the control group. (r=0.432; p=0.010).Conclusion: In conclusion, we found that scleral thickness did not change in corneal dystrophies. Further histological studies are needed to conclusively exclude microstructural alterations of scleral thickness in patients with corneal stromal dystrophies.
Keywords: Anterior scleral thickness; Corneal stromal dystrophy; Granular corneal dystrophy; Lattice corneal dystrophy; Macular corneal dystrophy